Email consultations in general practice - Ron Neville; Wendy Marsden; Colin McCowan; Claudia Pagliari; Helen Mullen; Allison Fannin (Journal of Innovation in Health Informatics, 2004)
Background Email is an established method of communication in business, leisure and education but not yet health care. Aim To evaluate an email service enabling communication between patients and their general practice regarding repeat prescriptions, appointment booking and clinical enquiries. Design Qualitative analysis of interactions and an electronic user survey. Setting An urban practice in Dundee, Scotland. Participants 150 patients aged 24 to 85. Methods We set up a practice facility to allow our patients to use email to book appointments, order repeat prescriptions and consult their general practitioner (GP). Results Patient satisfaction with the service was very high. Patients specifically commended the practice for setting up a facility to allow communication outside standard working hours and for the ease of ordering repeat prescriptions. Patients were pleased to have a means of seeking their doctor’s comment or opinion without bothering him or her by making and attending a formal face-to-face consultation. Email dialogue was polite, factual, but less formal than standard letters. Staff did not experience any perceptible rise in workload. Conclusions Use of an email consultation facility worked well within an urban practice, was deemed helpful by patients, and resulted in no apparent increase in GP workload. Our results suggest that there may be an unmet need amongst patients for clinical email services, and that such services may have positive outcomes for patients and practices.